Expresión plástica y motricidad fina en niños de 4 a 5 años, Unidad Educativa Dr. Manuel Agustín Cabrera Lozano, ciudad de Loja, periodo 2023- 2024 - Jimenez Tandazo, Gabriela Lisseth (2024)
Fine motor skills is a discipline related to the development of motor and cognitive abilities in children, combining elements and techniques of plastic expression to understand how muscle coordination produces small movements and influences their development. Therefore, the present research aimed to determine if plastic expression influences fine motor skills in children aged 4 to 5 years from the Dr. Manuel Agustín Cabrera Lozano Educational Unit, located in Loja city. A quasi-experimental research design was implemented, using plastic expression to demonstrate the effectiveness of fine motor skills, with both qualitative and quantitative approaches allowing for data collection and analysis. Inductive-deductive and analytical-synthetic methods were employed to investigate, collect, analyze, and interpret data from both variables to address the research objective and establish respective conclusions. Observation was utilized as the technique during activity execution, with the Battelle Developmental Inventory employed as the instrument. It was found that 78% of children faced difficulties in digital pinch pressure and coordination, placing them in the low level and delay category. Consequently, an activity guide based on plastic expression was designed, resulting in improvement and a decrease to 26% of children facing these difficulties. In conclusion, plastic expression offers significant benefits to fine motor skills as it strengthens the motor system and enhances agility for various daily activities among children. Keywords 5: art, techniques, precision, strategy, strokes